Sangha’s Opinions Towards the Sangha Administration: A Case Study of Sangha Administration Tambon Tha Mai, Samut Sakhon Province - บุญมี, ประกิต (Siam University Journal of Business Administration, 2022)
The objectives of this study were: 1) to study the sangha administration: a case study of sangha administration Tambon Tha Mai, Samutsakhon province 2) to compare sangha’s opinions towards the sangha administration: acase study of sangha administration Tambon Tha Mai, Samutsakhon province by classifying on the personal factors. The research was conducted by quantitative research. The sampling was conducted by collecting data from samples of 118 monks in temples in Tambon Tha Mai, Samutsakhon province. The statistics for analysis data used Frequency, Percentage, Mean Standard Deviation, and F-test with One Way ANOVA. Results of the research were 1) overall, the sangha administration: a case study of sangha administration Tambon Tha Mai, Samutsakhon province was at the high level (=3.89). Considering each aspect, it was found that monks having comments on the sangha administration: a case study of sangha administration Tambon Tha Mai, Samutsakhon province were at the high level. 2) the comparison from hypothesis testing, analysis of different variables, i.e., age, education level, including Pali and Dhamma education, results in no differences. Therefore, all hypotheses were denied.